When Civil Servants are Exposed to Radical Understandings: Analysis of State Apparatus Receptions about Reporting on Deradicalization Terrorism Programs on Metro TV - Afdal Makkuraga Putra; Raden Bagus Yuniadji; Heri Budianto; Riza Darma Putra (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
This study examines the public reception of reporting on the deradicalization of terrorism on Metro TV. The method to be used is reception analysis from the Stuart Hall model. Reception analysis is an alternative approach to studying audiences and how to interpret messages received from a media; the starting point of this research is the assumption that the meaning contained in mass media is not only found in the text. The subject of this research is civil servants in the Secretariat of the Vice President. The study results show that in the hegemonic-dominant position of acceptance, informants accept and share media values on the issue of radicalism. Informants agree with media statements that show the existence of radicalism in society and threaten the integrity of the Republic of Indonesia. The conflicting evidence is low because several events in Indonesia indicate the existence of activities that are considered radical. Weaker resistance to media messages means a relatively strong media position influencing informants' acceptance of the text. In the position of oppositional acceptance, the informants' political awareness and reactions to the construction of media information, especially the problems of radicalism and intolerance in Indonesia, are not easily influenced by the structure of media information.